Improving Student Learning Outcomes In Lessons Of History Of Islamic Civilization Through The Application Of Bingo Strategies - Widiani, Desti; Jiyanto, Jiyanto (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
Abstract. This article is a field research using the "Classroom Action Research" method. Learning the History of Islamic Civilization at MTs Muhammadiyah 1 Gemolong in class VII, found several problems, namely the teaching and learning process so far still tended to use the lecture method has not been varied with other methods. This results in student learning outcomes still low. Based on existing conditions, it is necessary to improve the learning process of teaching Islamic Civilization History. Therefore classroom action research is conducted to improve student learning outcomes in the subjects of Islamic Civilization History by applying bingo strategies. The purpose of this study is to improve student learning outcomes in the subjects of Islamic Civilization History and increase student activity in Islamic Civilization History subjects. The action hypothesis in this study is to apply the bingo strategy to improve student learning outcomes and student activities in Islamic Civilization History subjects. Based on the indicators of success of the actions determined from the 3 research cycles, the student learning outcomes reach the classical success limit (â‰¥ 85%) of all students who have achieved individual success (score â‰¥ 60) and most students (75%) actively engage in learning or The teacher has reduced his dominance in learning, showing that student learning outcomes in the subjects of History of Islamic Civilization through the application of bingo strategies can increase. Before the action is carried out the percentage of student success is 21%. In the first cycle student learning outcomes increased to 82%, while in the second cycle the percentage of success was 95% and in the third cycle the success of students reached 100%. Student activities on the subject of Islamic Civilization History through the application of increased bingo strategies, before the actions of passive students are carried out in learning activities and the teacher dominates in learning activities. In the first cycle the percentage of student activity was 68% with the criteria of good / very good, in the second cycle of 95% and in the third cycle student activity reached 100%. This shows that students are doing well / very well in learning the History of Islamic Civilization and the teacher has been reduced to dominate in learning activities. Thus the bingo strategy can be a solution to improve learning outcomes in Islamic Civilization History subjects.Keywords: Learning Achievement, Activity, Bingo Strategy.